ANALISA KEMACETAN PROGRAM BUMDES SUKA MAJU - br Siahaan, Shanti Veronica; Vuspitasari, Benedhikta Kikky (JPSI (Journal of Public Sector Innovations), 2020)
This research is motivated by a government program about accelerating village independence through the implementation of the BUMDes program activities that have not been running since 2017 in Suka Maju village, Sungai Betung District, Bengkayang Regency, West Kalimantan. The purpose of this research is to find out the causes of bottlenecks in the BUMDes program and to provide input for the village government in carrying out the next BUMDes program. This research uses descriptive qualitative research techniques conducted by direct observation, in-depth interviews, and documentation in which the research participants, namely the Village Head, the Village Head Officer, and the core management of BUMDes were selected by purposefull sampling. Testing the correctness of the data using triangulation techniques. The results showed that the non-progress of BUMDes activities that had been launched since the formation of BUMDes management in 2017 was due to human resource issues where the inadequate capacity of understanding and knowledge about BUMDes owned by the Village Head and BUMDes administrators made this program not yet a priority program for the government. Suka Maju village and also a lack of commitment to implementing the BUMDes program so that it has not been able to drive the village economy as expected.